Identification, characteristics and dynamics of Arctic extreme seasons - Hartmuth, Katharina; Boettcher, Maxi; Wernli, Heini; id_orcid:0 000-0001-9674-4837; Papritz, Lukas; id_orcid:0 000-0002-2047-9544 (Copernicus, 2022)
The Arctic atmosphere is strongly affected by anthropogenic warming leading to long-term trends in surface temperature and sea ice extent. In addition, it exhibits strong variability on timescales from days to seasons. While recent research elucidated processes leading to short-term extreme conditions in the Arctic, this study investigates unusual atmospheric conditions on the seasonal timescale. Based on a principal component analysis in the phase space spanned by the seasonal-mean values of surface temperature, precipitation and the atmospheric components of the surface energy balance, individual seasons are objectively identified that deviate strongly from a running-mean climatology and that we define as extreme seasons. Given the strongly varying surface conditions in the Arctic, this analysis is done separately in Arctic sub-regions that are climatologically characterized by either sea ice, open ocean or mixed conditions. Using ERA5 reanalyses for the years 1979–2018, our approach identifies two to three extreme seasons for each of winter, spring, summer and autumn, with strongly differing characteristics and affecting different Arctic sub-regions. Two extreme winters affecting the Kara and Barents seas are selected for a detailed investigation of their substructure, the role of synoptic-scale weather systems, and potential preconditioning by anomalous sea ice extent and/or sea surface temperature at the beginning of the season. Winter 2011/12 started with average sea ice coverage and was characterized by constantly above-average temperatures during the season related mainly to frequent warm air advection by quasi-stationary cyclones in the Nordic Seas. In contrast, winter 2016/17 started with reduced sea ice and enhanced sea surface temperatures in the Kara and Barents seas, which, together with increased frequencies of cold air outbreaks and cyclones, led to large upward surface heat flux anomalies and strongly increased precipitation during this extreme season. In summary, this study shows that extreme ...